2021
DOI: 10.1097/shk.0000000000001890
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Values of Platelet Distribution Width and Platelet Distribution Width-to-Platelet Ratio in Severe Burns

Abstract: Background: Platelet distribution width (PDW) and PDW-to-platelet ratio (PPR) have been proven to be good prognostic indicators for many diseases. However, their prognostic values in severe burns have not been reported. Objective: To investigate the early time course of PDW and PPR in severe burn patients and investigate their prognostic values. Methods: This is a 16-year, single-center retrospective study of 590 severe burn patients. The complete blood count parameters on day 1, day 3, and day 7 postburn, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 43 publications
3
7
0
2
Order By: Relevance
“…27 It has been showed PDW was an independent risk factor for 120-day mortality in severe burn patients. 28 Moreover, we found that burn wound area was also an independent factor associated with wound healing, which was consistence with previous study. 29 Besides wound healing, medical cost is another consideration for burn wound care.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…27 It has been showed PDW was an independent risk factor for 120-day mortality in severe burn patients. 28 Moreover, we found that burn wound area was also an independent factor associated with wound healing, which was consistence with previous study. 29 Besides wound healing, medical cost is another consideration for burn wound care.…”
Section: Discussionsupporting
confidence: 91%
“…A High PDW level indicts a higher production of larger reticulated platelets, which have larger and more metabolical activity, may promote the healing process of burn wound 27 . It has been showed PDW was an independent risk factor for 120‐day mortality in severe burn patients 28 . Moreover, we found that burn wound area was also an independent factor associated with wound healing, which was consistence with previous study 29 …”
Section: Discussionsupporting
confidence: 90%
“…Some studies have indicated that patients with severe sepsis/septic shock have lower platelet count [12]. The prognostic ability of platelet count-related indices has been investigated in a variety of diseases, such as cancers, sepsis and liver cirrhosis [13][14][15][16]. The platelet count-related ratios may be a more promising biomarker of inflammation than conventional indicators.…”
Section: Introductionmentioning
confidence: 99%
“…Essa ativação, faz com que os fragmentos fiquem esféricos e exibam pseudópodes durante o processo de ativação para facilitar a aderência a outras plaquetas e a células lesadas, aumentando os valores da largura de distribuição de plaquetas (PDW) e volume plaquetário médio (VPM). Caso o estado do paciente continue a agravar, maior a proliferação heterogênea de megacariócitos e maior a presença de ativação plaquetária (Lin et al, 2021).…”
Section: Alterações Plaquetáriasunclassified
“…A quantificação da linhagem imatura por meio do Delta Neutrophil Index (DNI) reflete o estímulo medular intenso (Ahn, 2018). Já o fenômeno de ativação plaquetária pode ser identificado a partir da verificação do Volume Plaquetário médio (VPM) e Platelet Distribution Width (PDW), ambos associados a formação de eventos trombóticos juntamente com a redução do nível plaquetário (Lin et al, 2021). Outros parâmetros hematológicos, como as razões leucocitárias, avaliam a depleção de linfócitos associado à contagem de plaquetas e neutrófilos, refletindo as complicações originadas pelo distúrbio (Hou, 2021).…”
Section: Introductionunclassified